Virginal Breast Hypertrophy and Symptomatic Treatment: A Case Report - Ebru Menekşe; Safa Önel; Faruk Karateke; Koray Daş; İlhan Bali; Hilmi Bozkurt; Selim Sözen; Mehmet Özdoğan (European Journal of Breast Health, 2014)

(untitled)
Virginal breast hypertrophy is a rare benign disease. It is characterized by rapid and excessive growth of one or two breasts during peripubertal period. There is no specific treatment algorithm, subcutaneous mastectomy and prosthesis replacement, reduction mammoplasty, medical treatment with particularly tamoxifen are all recommended in the literature. Unfortunately, all treatment methods have some disadvantages in this patient group who have not completed their sexual and physical maturation. Although these treatments are usually required, it should be noted that spontaneous remission could rarely be seen in virginal hypertrophy. We aimed to present a case of virginal hypertrophy, in whom symptomatic treatment has been used and breast growth regressed spontaneously.